If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + 10n = 2 + 3(8 + 4n) 24 + 10n = 2 + (8 * 3 + 4n * 3) 24 + 10n = 2 + (24 + 12n) Combine like terms: 2 + 24 = 26 24 + 10n = 26 + 12n Solving 24 + 10n = 26 + 12n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-12n' to each side of the equation. 24 + 10n + -12n = 26 + 12n + -12n Combine like terms: 10n + -12n = -2n 24 + -2n = 26 + 12n + -12n Combine like terms: 12n + -12n = 0 24 + -2n = 26 + 0 24 + -2n = 26 Add '-24' to each side of the equation. 24 + -24 + -2n = 26 + -24 Combine like terms: 24 + -24 = 0 0 + -2n = 26 + -24 -2n = 26 + -24 Combine like terms: 26 + -24 = 2 -2n = 2 Divide each side by '-2'. n = -1 Simplifying n = -1
| b+18=-5 | | 20=-14+n | | x+2*4=6 | | (2x-1)=(x+5) | | x^2+3*x=40 | | f(-2)=x+3 | | 7x+6=8(x-4) | | 45+5n=10(8n-2)-10n | | 5x+7(x-14)=5(x-14) | | 10(2n-3)=(10n+6)+4 | | y=3x^2-4x-6 | | 36-25x^2=0 | | y=x^2-6 | | 3x+12=7*3 | | 4x+(x-9)=4(x-10) | | 6(3n-5)=(9n+8)+5 | | ax+2=aw | | 4=t-5s | | 5n-8=-48 | | (x^3+4x^2)-(2x-8)=0 | | 3n-9=-27 | | 3-6(4+8n)=-21+10n | | 20r^2-41r+20=0 | | x(10x+24)=0 | | (s+16)(s+81)=0 | | 7-3x=15+5x | | 3-6(4+8n)=21+10n | | c(c+3)=0 | | y-(2y-5)=94 | | (3s+7)(s+6)=0 | | (3)-(-4)= | | s^2+11s+24=0 |